2020
DOI: 10.14393/bj-v36n3a2020-47729
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy induction in Physalis alkekengi

Abstract: Physalis alkekengi is an ornamental plant that can also be used as a medicinal plant due to its anti-inflammatory, bactericidal, antitumor and fungicidal properties. Polyploidization can be an important tool in the genetic improvement of this species. The objective this work was to obtain tetraploids in vitro and to evaluate the phytotechnical traits of P. alkekengi. For this, nodal segments of P. alkekengi var. Franchettii were inoculated into petri dishes containing 100 ml of MS medium supplemented with colc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Polyploidization using nodal segments of P. alkekengi var. Franchettii showed that MS medium supplemented with 0.08% colchicine for 24 h resulted tetraploides plant [27]. However, until now no one has reported the effect of colchicine on the profile and content of withanolides especially in Physalis plants.…”
Section: Introductionmentioning
confidence: 99%
“…Polyploidization using nodal segments of P. alkekengi var. Franchettii showed that MS medium supplemented with 0.08% colchicine for 24 h resulted tetraploides plant [27]. However, until now no one has reported the effect of colchicine on the profile and content of withanolides especially in Physalis plants.…”
Section: Introductionmentioning
confidence: 99%
“…The Cape gooseberry, Physalis peruviana L. (Solanaceae), is native to the Andean region and is commercially grown in Brazil (MUNIZ et al, 2014) due to its pharmacological and nutritional benefits (SANTOS et al, 2020). It has also become an attractive alternative for small farmers seeking to diversify their crops because of the high added value of its fruits and its low costs of cultivation (PUENTE et al, 2011).…”
mentioning
confidence: 99%